The Effects of Aging and Physical Activity on Doppler Measures of Diastolic Function - Prasad, Anand; Popovic, Zoran B.; Arbab-Zadeh, Armin; Fu, Qi; Palmer, Dean; Dijk, Erika; Greenberg, Neil L.; Garcia, Mario J.; Thomas, James D.; Levine, Benjamin D. (The American journal of cardiology, 2007)
Healthy aging results in changes in Doppler measures of diastolic function. It is unclear whether these alterations are a specific manifestation of the aging process or reflect a cardiac adaptation to a more sedentary lifestyle. It was hypothesized that healthy, but sedentary, aging would result in slowing of diastolic filling and myocardial relaxation, whereas lifelong endurance training would prevent such changes. Doppler data were measured in young subjects and sedentary and fit seniors across a broad range of loading conditions. Thirteen sedentary healthy (70 ± 4 years) and 12 fit Masters athlete (68 ± 3 years) seniors were recruited. Twelve young healthy (32 ± 9 years) subjects were used for comparison. Pulmonary capillary wedge pressure and Doppler variables were measured at the 6 loading conditions of baseline (twice), −15 and −30 mm Hg lower body negative pressure, and 2 levels of saline solution infusion. Doppler variables consisted of early and late mitral inflow velocity (E/A) ratio, isovolumetric relaxation time (IVRT), tissue Doppler velocities (TDI E mean), and propagation velocity of mitral inflow. Aging resulted in a decrease in E/A ratio (p <0.001), TDI E mean (p <0.001), and propagation velocity of mitral inflow (p <0.001) and an increase in IVRT (p = 0.001). Lifelong endurance training did not completely prevent the changes in E/A ratio (p = 0.212), IVRT (p = 0.546), or propagation velocity of mitral inflow (p = 1.00). Fit seniors were able to achieve E/A ratios of 1.0 during baseline and saline solution infusion. TDI E mean was higher in fit versus sedentary seniors at baseline (p = 0.012) and during maximal lower body negative pressure (p = 0.036), but not during saline solution infusion (p = 0.493). In conclusion, age-associated abnormalities in Doppler measures of myocardial filling and relaxation are only partially minimized by lifelong endurance training and therefore may be more specific to the aging process than secondary to years of deconditioning.